Bruce promised workers a 44-hour week, a housing scheme, child endowment, national insurance. He gave them the Crimes Act, perverted arbitration, gaol for unionists, government free-labor, unemployment
All text; orange and white text over black background; cartoon portraits of Stanley Bruce PO-2056